2022
DOI: 10.1021/acs.jnatprod.1c01003
|View full text |Cite
|
Sign up to set email alerts
|

Aspulvins A–H, Aspulvinone Analogues with SARS-CoV-2 Mpro Inhibitory and Anti-inflammatory Activities from an Endophytic Cladosporium sp.

Abstract: Eight new aspulvinone analogues, aspulvins A–H ( 1 – 8 ) and aspulvinones D, M, O, and R ( 9 – 12 ), were isolated from cultures of the endophytic fungus Cladosporium sp. 7951. Detailed spectroscopic analyses were conducted to determine the structures of the new compounds. All isolates displayed different degrees of inhibitory activity against the severe acute respiratory syndrome coronavirus 2 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…After 10 min of incubation, the relative fluorescence unit (RFU) was read on a microplate reader (DU-730; Beckman Coulter, Brea, CA, USA) at the excitation of 340 nm and the emission of 490 nm. The calculation formula for inhibition rate is consistent with the previous report [ 25 ].…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…After 10 min of incubation, the relative fluorescence unit (RFU) was read on a microplate reader (DU-730; Beckman Coulter, Brea, CA, USA) at the excitation of 340 nm and the emission of 490 nm. The calculation formula for inhibition rate is consistent with the previous report [ 25 ].…”
Section: Methodssupporting
confidence: 86%
“…Liang et al have discovered the aspulvinone analogs as the potential inhibitors using a beyotime enhanced inhibition kit. The IC 50 values of aspulvinones D, M, and R are 10.3 ± 0.6, 9.4 ± 0.6, and 7.7 ± 0.6 μM, respectively [ 25 ]. In the previous reports, the IC 50 of ebselen was different from different reports such as 0.67 ± 0.09 μM [ 4 ] and 0.04 ± 0.004 μM [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the fungus was isolated from Paris polyphylla var. yunnanensis, a medicinal plant collected in Kunming, China [154].…”
Section: Anti-sars-cov-2mentioning
confidence: 99%
“…M pro plays an essential role in the replication and transcription of SARS-CoV-2. There are a number of microbe-produced natural products with the ability to inhibit M pro , including aurasperone A [152]; neoechinulin A [153]; as well as aspulvinone D, M, and R [154].…”
Section: Possible Targetmentioning
confidence: 99%
“…6 Recently, a study showed that some aspulvinones could inhibit SARS-CoV-2 infection and reduce inammatory reactions caused by SARS-CoV-2. 7 As part of our work, aspulvinone O and H were isolated from the rice culture of Aspergillus terreus and identied as potent bioactive inhibitors of GOT1 and novel anti-tumor agents for PDAC therapy. 8,9 However, the poor isolated yield and limited structure variation restricted our further study of their pharmaceutical properties.…”
Section: Introductionmentioning
confidence: 99%